The structure of the perceived professional identity of Japanese public health nurses - Iwasaki, Riho; Kageyama, Masako; Nagata, Satoko (Public health Nursing, 2018)
Objective As health problems become more diverse and complicated, the way public health nurses (PHNs) work is changing. Research at the conceptual level of professional identity of PHNs is lacking. This study aimed to explore the structure of the perceived professional identity of Japanese PHNs. Design and Sample Grounded theory method was used. Twenty‐five PHNs in Japanese municipalities were participated in the study. Measurements Data were collected through semistructured interviews and analyzed using open, axial, and selective coding. Results Three categories emerged: (1) providing support to the consulter directly, (2) working as a member of the administrative organization, and (3) working for all residents to improve community development. The modality of perceived professional identity showed interindividual and intraindividual differences and was either stable or unstable. The perceived professional identities coexisted, but there was a conflict between (1) and (2). Conclusion PHNs should be made aware of the three identities revealed in our study and the possibility of a conflict between identities. Moreover, to ensure working for all residents to improve community development, a population‐based approach to education is needed with cooperation of universities and clinical practice.